Analisis Spasial dan Pemetaan Zonasi Penggunaan Lahan di Kota Gorontalo Berbasis Sistem Informasi Geografis - Irawaty Hadi; Ramla Hartini Melo; Sri Endang Saleh (-, 2026)
This study aims to analyze land use patterns and map land use zoning in Gorontalo City based on a Geographic Information System (GIS). The method used was spatial analysis with a quantitative descriptive approach through the processing of spatial data in the form of satellite imagery, administrative maps, and land use data. The research stages included digitization, classification, image interpretation, and overlay techniques using GIS software to identify the distribution and patterns of land use in each district. The results showed that residential areas dominate the city center, such as South Kota, Central Kota, and Sipatana districts, due to the high concentration of economic, governmental, educational, and commercial activities. Meanwhile, forests, plantations, rice fields, and shrubland are more widely distributed in the suburban areas, such as Hulonthalangi, Dumbo Raya, and North Kota districts. The conversion of natural and agricultural land into built-up areas indicates rapid urban development. The application of GIS in this study was able to provide accurate spatial information regarding land use zoning, which can support spatial planning, development control, and environmental sustainability efforts in Gorontalo City.